Community Response to Government Policies at The Potential Landslide Area: The Case in Kuloprogo Regency - Donie, Syahrul (Universitas Muhammadiyah Surakarta, 2014)
The study examined the extent of community appreciation or response to government policies at the potential lanslide areas and the influencing reasons. By interviewing 35 representative informants, men and women, and divided into old, young and adult, then the data are analyzed and interpreted using the theory of action and the theory of symbolic. The results showed, the community, dominated by the farmer, were able to respond and deeply understood the government policies, particularly policies of spatial planning. This was indicated by the increasing knowledge of the community against areas that were prone to landslide and other sign that the region was going to experience a landslide. Almost all respondents said that they live in hilly areas prone to landslides, and they knew how to cope with and respond to these signs. However, government policy declaring that the community were expected to move from the area considered as dangerous was still lack of communityâs attention. This was due to the undersired experiences of the community in the new area which did not make their lives better, both in terms of livelihood as well as in terms of their social-culture life.